2005
DOI: 10.1128/cdli.12.11.1311-1316.2005
|View full text |Cite
|
Sign up to set email alerts
|

Selected RD1 Peptides for Active Tuberculosis Diagnosis: Comparison of a Gamma Interferon Whole-Blood Enzyme-Linked Immunosorbent Assay and an Enzyme-Linked Immunospot Assay

Abstract: We recently set up a gamma interferon (IFN-␥) enzyme-linked immunospot assay (ELISPOT), using selected early secreted antigenic target 6 (ESAT-6) peptides, that appears specific for active tuberculosis (A-TB). However, ELISPOT is difficult to automate. Thus, the objective of this study was to determine if the same selected peptides may be used in a technique more suitable for routine work in clinical laboratories, such as whole-blood enzyme-linked immunosorbent assay (WBE). For this purpose, 27 patients with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
3
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 28 publications
(40 reference statements)
4
77
3
3
Order By: Relevance
“…In nine of these, TST positivity was significantly associated with BCG vaccination as an independent predictor in multivariate analysis [47,50,55,62,67,71,72,74,77] with odd ratios ranging between 3.8 (95% CI 1.0-13.9) [50] [35] GOLETTI [36] JAFARI [37] JAFARI [38] KAMPMANN [39] KANG [40] LEE [41] MARKOVA [42] WANG [43] DETJEN [26] DHEDA [34] GOLETTI [36] KAMPMANN [39] KANG [40] MARKOVA [42] odds for test positivity with M. tuberculosis exposure gradients, or using chest radiography lesions as a surrogate of prior exposure, the IGRAs associated better with exposure than the TST, irrespective of the setting's disease burden. Furthermore, there was generally a poor agreement between IGRAs and TST results (for k statistics, see table 3).…”
Section: Ppv For Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…In nine of these, TST positivity was significantly associated with BCG vaccination as an independent predictor in multivariate analysis [47,50,55,62,67,71,72,74,77] with odd ratios ranging between 3.8 (95% CI 1.0-13.9) [50] [35] GOLETTI [36] JAFARI [37] JAFARI [38] KAMPMANN [39] KANG [40] LEE [41] MARKOVA [42] WANG [43] DETJEN [26] DHEDA [34] GOLETTI [36] KAMPMANN [39] KANG [40] MARKOVA [42] odds for test positivity with M. tuberculosis exposure gradients, or using chest radiography lesions as a surrogate of prior exposure, the IGRAs associated better with exposure than the TST, irrespective of the setting's disease burden. Furthermore, there was generally a poor agreement between IGRAs and TST results (for k statistics, see table 3).…”
Section: Ppv For Progressionmentioning
confidence: 99%
“…NPV in patients with active tuberculosis 18 articles satisfied our inclusion criteria for evaluating the NPV; 13 assessed the NPV among confirmed tuberculosis cases [22,26,[34][35][36][37][38][39][40][41][42][43][44] and six assessed the prospective outcome in IGRA-negative individuals after an average of 2 yrs [19-22, 45, 46]. Among the studies in which the NPV was evaluated in patients with confirmed tuberculosis (387 tuberculosis cases with a valid T-SPOT1.TB result and 304 with valid QFT-G-IT result), the NPV varied greatly, irrespective of the IGRA used.…”
Section: Specificitymentioning
confidence: 99%
“…However, the relevance of these results is debatable since, for the clinician, the challenge is not to distinguish between subjects who are naive to TB exposure versus active TB, but rather to distinguish active from latent disease among subjects who probably have been infected. Several studies have consistently shown higher production of IFN-c by lymphocytes challenged by M. tuberculosis-specific antigens in culture-proven active TB than in LTBI [16][17][18][19]. GOLETTI et al [19] compared the results of different IGRAs in patients with clinical suspicion of TB according to outcome (culture-proven TB versus alternative diagnosis established or resolution of clinical symptoms without drugs active against TB).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a gold standard for LTBI, active TB is used as a surrogate for LTBI. FIGURE 2 shows forest plots of sensitivity and specificity (for active disease) from studies that used the research or commercial versions of the QFT-G and T-SPOT.TB assays [23][24][25][26][27][28][29][30][31][32][33]. Overall, the plot shows high specificity (>95% in most studies).…”
Section: Summary Of Research Evidence On Test Performancementioning
confidence: 99%